2002
DOI: 10.1038/sj.onc.1205488
|View full text |Cite
|
Sign up to set email alerts
|

Distinct epigenetic phenotypes in seminomatous and nonseminomatous testicular germ cell tumors

Abstract: The genetic nature of testicular germ cell tumors and the molecular mechanisms underlying the morphological and clinical differences between the two subtypes, seminomas and nonseminomas, remains unclear. Genetic studies show that both subtypes exhibit many of the same regional genomic disruptions, although the frequencies vary and few clear differences are found. We demonstrate significant epigenetic differences between seminomas and nonseminomas by restriction landmark genomic scanning. Seminomas show almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
121
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 29 publications
19
121
0
1
Order By: Relevance
“…This may suggest that the total effect on expression levels of mechanisms other than chromosomal imbalances is similar in the different subtypes of TGCT. This is despite reported differences in the frequency of CpG island methylation of 0.08% in SE compared to 1.11% in NS (Smiraglia et al, 2002;Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This may suggest that the total effect on expression levels of mechanisms other than chromosomal imbalances is similar in the different subtypes of TGCT. This is despite reported differences in the frequency of CpG island methylation of 0.08% in SE compared to 1.11% in NS (Smiraglia et al, 2002;Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 65%
“…Factors predicted to influence gene expression include genomic copy number and epigenetic factors such as methylation. The level of methylation in TGCT varies between the subtypes and previous studies have found that SE have a lower level of CpG island methylation than NS (Smiraglia et al, 2002;Zhang et al, 2005).…”
mentioning
confidence: 94%
“…This is in line with previously described differences in the epigenetic phenotype of SEMs and N-SEMs. The genome of N-SEMs appears to be more methylated than that of both CIS and SEMs (Smiraglia et al, 2002;Smith-Sorensen et al, 2002;Honorio et al, 2003). Teratomas are more differentiated than EC and the absence of DMNT3L expression in teratomas in the RT -PCR analysis could indicate that a demethylation of DNA occurs when an EC differentiates into a teratoma.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, DNA methylation seems to be a major mechanism for regulating gene expression in TGCT. [22][23][24] Finally, the expression of NKX3.1 seen in a subset of the most differentiated nonseminomas indicates that the loss of its expression in TGCT is reversible and thus likely caused by epigenetic silencing. The fact that none of the 70 embryonal carcinomas expressed NKX3.1 and the general view that the embryonal carcinomas are precursors for the differentiated nonseminomas support this assumption of reversibility.…”
Section: Discussionmentioning
confidence: 99%